Effect of initial starvation on the larval development of the edible portunid crab Thalamita crenata (Latreille) - Kannupandi, T; Krishnan, T; Soundarapandian, P; Shanmugam, A (Indian Journal of Fisheries, 2011)
The effect of early starvation on larval survival and development duration inThalamita crenata was studied. Initial feeding for 3 days was sufficient for allthe zoea I to moult successfully to zoea II without further feeding. Point of ReserveSaturation for 50% of individuals (PRS50) was approximately 1.6 days. Starvationperiods beginning right after hatching of zoea I prolonged the instar and Pointof-No-Return for 50% of individuals (PNR50) was also approximately 1.6 days.Delay in feeding delayed the development and reduced the survival.